Book Reviews (Journal of Finance, 1993)
Book reviewed in this article: International Banking Deregulation: The Great Banking Experiment . By RICHARD DALE Mortgage … Mortgage‐Backed Securities Markets . By FRANK J. FABOZZI and FRANCO MODIGLIANI Financial Derivatives . By ROBERT W. KOLB From Bleck‐Scholes to Black Holes . Edited by RISK/FINEX